Leadership Styles and Their Effects on Employee Satisfaction in Empowering Happiness at Workplace - Sam, Toong Hai; Isa, Khairunesa; Siqi, Peng; Palpanadan, Sarala Thulasi; Hong, Heng Chin; Luan, Ng Miew (Journal of Ecohumanism, 2025)
This paper explores the intricate relationship between leadership styles and employee happiness, presenting a comprehensive guide for leaders aiming to foster happiness in the workplace. Drawing upon theories of positive psychology and organizational behavior, we delve into the impact of leadership behaviors, such as empathy, support, and autonomy, on employee well-being and job satisfaction. This paper presents the main concepts and theories underpinning the research, including transformational leadership, inspirational, servant, autocratic and authentic leadership, to support the findings. This quantitative study involved 400 people from public sector companies, ranging in employment grades from 41 to 54, who were selected at random for the study. The data were analyzed descriptively by identifying and categorizing themes related to the leadership styles employed within the employees' organizations. The study reveals that Transformational, Authentic, Inspirational, and Servant Leadership styles have a positive impact on workplace happiness through traits such as empowerment, trust, and support, while Autocratic Leadership has a harmful effect due to its rigid and pressure-inducing nature. Organizations should focus on positive leadership styles and steer away from Autocratic approaches to improve employee happiness at work. The study uniquely highlights how Transformational, Authentic, Inspirational, and Servant Leadership styles contribute to workplace happiness, providing valuable guidance for organizations to foster a supportive work environment while mitigating the negative effects of Autocratic Leadership.